Between the Signposts: Thematic Interpolation and Structural Defamiliarization in Prokofiev's Sonata Process. (10th May 2020) - Perry, Rebecca
Abstract: This article explores the manner in which Prokofiev's interpolation of unrelated material in the middle of a traditional theme-space ironizes a seemingly normative sonata process in the first movement of his Second Piano Sonata (1912). By serving as the motivic, tonal, and rhetorical source of much that follows, this interpolation launches a quietly subversive counternarrative that threatens to undermine the traditional sonata narrative upon which the P theme had embarked. I invoke Russian Formalist literary theory as a framework for clarifying and contextualizing the disruptive structural function of Prokofiev's interpolations within his larger sonata text.